Banking and financial institutions : a guide for directors, investors, and counterparties - Gup, Benton E. (Hoboken, N.J. : Wiley, 2011)
"This book is a breakdown of the structure of banks and how they work for investors and prospective borrowers. Analyzing bank financial statements, such as Uniform Bank Performance Report (UPBRs), requires considerable knowledge of bank operations. Borrowers and other bank customers should need this knowledge of banking in order to facilitate their borrowing/lending process and the pricing of the products that they use. Banking products include traditional loans and deposits, as well as stock brokerage and investments, insurance, payment systems services, wealth management, and other services related to finance are also part of banking and need to be understood in its entirety for efficient bank work flow."--Provided by publisher.
Includes bibliographical references and index.
Business Administration
Keywords: Banks and banking -- United States; Financial institutions -- United States